(untitled) (Pursuits: A Journal of English Studies, 2025)
This paper discusses rhetoric’s historical evolution and theoretical foundations and criticism to scrutinize the significance of rhetoric criticism for oral and written discourse analysis. It emphasizes the lineage of classical rhetoric and its essential progression into contemporary rhetorical practices. These practices demonstrate the use of symbols as strategic and intentional tools for human communication, tracing their significant development from Ancient Greece through Rome to today’s frameworks. Prominent figures such as Corax, Aristotle, Cicero, and Quintilian are critically examined for their pivotal contributions to rhetorical theory and its undeniable relevance to civic life. The paper effectively dissects Aristotle’s framework of rhetoric, which encompasses three forms and three appeals: ethos, pathos, and logos, all vital components of persuasive language. Furthermore, the text addresses the transformative shift in communication modes during the Middle Ages and the Renaissance, wherein rhetoric became predominantly focused on philosophy, literature, and politics. In the present day, the scope of rhetoric has unequivocally expanded to include verbal, nonverbal, kinesthetic, and visual dimensions of communication. The paper also analyzes the critical methodologies employed in rhetorical criticism, highlighting the crucial role of the rhetorical critic in interpreting and evaluating rhetorical artifacts. Investigating various traditions and contemporary adaptations underscores the lasting significance of rhetoric across multiple disciplines, effectively connecting classical principles with modern communicative practices.